Investigation of Inaccuracies in the Assessment of Ventricular Late Potentials Using 12-lead ECG Recordings - Solieman Hanadi; Trong Tuyen Nguyen (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Ventricular late potentials (VLP) are predictors of cardiac disorders such as sudden death syndrome, myocardial infarction and ventricular tachyarrhythmias. Therefore, VLP assessment allows the severity and possible dangerous consequences of such disorders to be predicted.Aim. To determine errors associated with VLP assessment by high-resolution 12-lead ECG recordings.Materials and methods. VLPs were determined by the modulus of the cardiac electrical vector using signals from orthogonal leads. The conversion error was assessed using synchronous ECG recordings of 12-channel and orthogonal leads, the method of digital filtering (to reduce noise and interference) and the method of identifying characteristic points of the QRS complex and VLPs.Results. The conversion of 12-lead ECG signals into orthogonal signals results in errors associated with the assessment of both the modulus of the cardiac electrical vector and all VLP indicators. The Kors transformation was shown to provide the minimum errors when assessing the cardiac electrical vector modulus in the QRS area, with the errors related to the VRMS assessment not exceeding 0.084 %. The estimation of the QRSd and LAS errors should consider the nature of VLP variations and the zone of uncertainty in their assessment. The ambiguity of the results of assessing the boundaries of violations and the absence of pathologies in cardiac ventricular depolarization indicates the influence of a large number of factors on research accuracy. Errors in the assessment of these factors may result in under- and overestimation of dangerous heart rhythm disturbances and incorrect prediction of the patient' state.Conclusion. The obtained results can be used for reducing errors associated with the assessment of VLP indicators, improving the diagnostic accuracy of dangerous heart rhythm disturbances and predicting disease exacerbation due to structural and morphological disorders of the myocardium.